Empowerment of Family Assistance Teams Through IMAH GIZI Modeling in the Stunting Locus of Tasikmalaya Regency: Pemberdayaan Tim Pendamping Keluarga Melalui Pemodelan IMAH GIZI di Lokus Stunting Kabupaten Tasikmalaya - Sinta Fitriani; Hariyani Sulistyoningsih; Wuri Ratna Hidayani (Universitas Lancang Kuning, 2024)
Stunted toddlers in Cikunir Village have increased from 88 toddlers in 2020 to 107 toddlers in 2022. As many as 26.78% of pregnant women at risk and 42% of stunted toddlers in Cikunir Village have received assistance. The family assistance team (TPK) has an important role in mapping stunting risk groups and assisting families in stunting recovery, so efforts need to be made to increase the capacity of the TPK in carrying out its role. The activities carried out took the form of training as an effort to increase the capacity of the family assistance team in detecting risk groups as well as family assistance in the form of IMAH Gizi modeling. The results of the activity showed that there was an increase in the capacity of the accompanying team after attending training on anthropometric measurements, surveillance and counseling communication. Apart from that, the accompanying team was able to provide family assistance by establishing the IMAH Gizi model in three hamlets. This community empowerment activity through training and nutritional modeling can be expanded and replicated in other localities so that it can help local governments in mapping stunting risk groups and facilitate interventions to assist stunting risk groups.